Features of the Organisation of Illegal Book Printing of the Fedoseyevtsy Old Believers in the Second Half of the 19th — Early 20th Centuries - Irina Viktorovna Pochinskaya (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2023)
This article attempts to analyse the book publishing activities of the Bespopovtsy Old Believers in the second half of the nineteenth century. The Old Believer book printing of this period is the least studied section in the history of Russian printed books. From its inception in the early eighteenth century until 1905, the book publishing of the Old Believers was illegal. If the period of the eighteenth — early nineteenth centuries is clear enough, there is only a certain general idea of the situation in the second half of the nineteenth — early twentieth centuries (before 1905). The reason for this is that all editions of the latter period are anonymous or have false imprints. The author of the article offers her own approach to the study of this stage of Old Believer printing. In her opinion, it is necessary to identify and describe publications with their subsequent grouping based on the commonality of some features, primarily fonts and ornamentation, with a further search for ways to link these book groups to printing houses known from archival documents. Following this approach, the article identifies a group of publications, which list Pochaev as their place of publication. An analysis of these publications and identified archival materials makes it possible to identify eight printing houses in which they were printed. The study results in the following hypothesis: all these printing houses belonged to the Old Believers of the Fedoseyevtsy denomination, they closely interacted with each other, forming a kind of network, whose activities were guided and inspired by the Preobrazhensky cemetery. A special role in the production of printed materials of the Fedoseyevtsy denomination was played by the printing house of the Ovchinnikov brothers, which functioned for about 35 years. It helped smaller printing houses, cast fonts for them, made decor clichйs, and received materials from closed establishments. After the Ovchinnikov printing house ceased operations, other printers took over from them, who probably studied with them and purchased their equipment.